Optical film and image display device using same

By forming a hard coating composed of methacrylic monomer, polymer and thiol compound in a specific proportion on the transparent substrate of the image display device, the back-reverse problem of the optical film when taking into account both hardness and bending properties is solved, and high An optical film with hardness, low curlability and high bending properties is suitable for image display devices of portable terminals.

CN119173391APending Publication Date: 2024-12-20TOPPAN HOLDINGS INC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380039006.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-17
Filing Date
2023-04-25
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

When the optical film used in the conventional image display device takes into account both high hardness and high bending properties, there is a relationship between hardness and bending properties. Moreover, due to the shrinkage of the cured layer, it is difficult to take into account both high hardness and low bending properties.

Method used

On at least one surface of the transparent substrate, the hard coating layer consists of a methacrylic monomer having three or more methacryloyl groups, a methacrylic polymer having two or more methacryloyl groups, and a thiol compound having two or more methacryloyl groups, and a thiol compound The composition of the cured film has a ratio of methacrylic acid monomers of 60 to 85%, the ratio of methacrylic acid polymers of 5 to 35%, the ratio of thiol compounds of 0.5 to 9%, and the film thickness is 3 to 20 μm.

Benefits of technology

The optical film with high bending and high hardness is realized, and the curling phenomenon is reduced, and it is suitable for folding image display devices of portable terminals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173391A_ABST
    Figure CN119173391A_ABST
Patent Text Reader

Abstract

The present invention provides an optical film having high bendability and high hardness, and reduced curl, and an image display device using the same. An optical film having a hard coat layer on at least one surface of a transparent substrate, the hard coat layer is a cured film of a composition containing (A) a (meth) acrylic monomer having three or more (meth) acryloyl groups in one molecule, (B) a (meth) acrylic polymer having two or more (meth) acryloyl groups in one molecule and having a weight-average molecular weight of 15,000-50,000, and (C) a thiol compound, the content of the (meth) acrylic monomer in the total solid content of the composition being less than or equal to 1% in the total solid content of the composition, and the content of the (meth) acrylic polymer in the total solid content of the composition being less than or equal to 1% in the total solid content of the composition. The content ratio of the (meth) acrylic monomer is 60-85% by mass, the content ratio of the (meth) acrylic polymer is 5-35% by mass, the content ratio of the thiol compound is 0.5-9% by mass, and the film thickness of the hard coat layer is 3-20 [mu] m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical film and an image display device using the same. Background Art

[0002] In image display devices such as liquid crystal displays and organic EL displays, an optical film having a hard coat layer provided on a resin film is used.

[0003] For example, Patent Document 1 describes a hard coating film formed on one or both sides of a transparent substrate using a composition containing a dendrimer compound having a (meth)acrylate terminal group, a polyhedral oligomer silsesquioxane compound having a (meth)acrylate terminal group, a photoinitiator, and a solvent.

[0004] Patent Document 2 describes a polarizer protective film formed by curing a resin composition containing a multifunctional acrylate monomer, an acrylate oligomer, an acrylate elastic polymer, and a photoinitiator.

[0005] Patent Document 3 describes an ultraviolet curable hard coating agent containing a polyfunctional urethane (meth)acrylate oligomer, colloidal silica modified with an acrylic group, a polyfunctional thiol compound, and a photopolymerization initiator.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent No. 7002895

[0009] Patent Document 2: Japanese Patent No. 6455993

[0010] Patent Document 3: Japanese Patent Application Publication No. 2016-11365 Summary of the invention

[0011] Technical problem to be solved by the invention

[0012] In recent years, in order to balance the large-scale display screen and the miniaturization of the device size, portable terminals with foldable image display devices are being developed. Optical films used in foldable image display devices require high flexibility in addition to high hardness. However, hardness and flexibility are usually in a trade-off relationship, and there is a problem that the higher the hardness of the material, the worse its flexibility.

[0013] In addition, an optical film having a cured layer of acrylic resin disposed on a resin film curls due to shrinkage during curing. The curling of the optical film is particularly strong when a high-hardness acrylic material is used. It is possible to replace a portion of the high-hardness acrylic material with a low-curling acrylic material, but in this case, although curling is suppressed, there is a problem of reduced hardness.

[0014] Therefore, an object of the present invention is to provide an optical film having high bendability and high hardness and reduced curling, and an image display device using the same.

[0015] Means for solving technical problems

[0016] The optical film of the present invention has a hard coating layer on at least one surface of a transparent substrate, and the hard coating layer is a cured film of a composition containing (A) a (meth)acrylic acid monomer having three or more (meth)acrylic groups in one molecule, (B) a (meth)acrylic acid polymer having two or more (meth)acrylic groups in one molecule and a weight average molecular weight of 15,000 to 50,000, and (C) a thiol compound, wherein the content of the (meth)acrylic acid monomer is 60 to 85% by mass, the content of the (meth)acrylic acid polymer is 5 to 35% by mass, and the content of the thiol compound is 0.5 to 9% by mass in the total solid content of the composition, and the film thickness of the hard coating layer is 3 to 20 μm.

[0017] The image display device of the present invention includes the above-mentioned optical film.

[0018] Effects of the Invention

[0019] According to the present invention, it is possible to provide an optical film having high bendability and high hardness and reduced curling, and an image display device using the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a cross-sectional view showing a schematic structure of an optical film according to an embodiment. DETAILED DESCRIPTION

[0021] The following is an explanation of the embodiments of the present invention. In this specification, "(meth)acrylate" is a general term for both acrylate and methacrylate, and "(meth)acryloyl" is a general term for both acryloyl and methacryloyl. Similarly, "(meth)acrylic acid" is a general term for both acrylic acid and methacrylic acid.

[0022] Figure 1 It is a cross-sectional view showing a schematic structure of an optical film according to an embodiment.

[0023] The optical film 1 includes a transparent substrate 2 and a hard coating layer 3 laminated on one surface of the transparent substrate 2 .

[0024] The transparent substrate 2 is a film serving as a base of the optical film and is formed of a material having excellent visible light transmittance. As the material for forming the transparent substrate, triacetyl cellulose, polyethylene naphthalate, polyethylene terephthalate, cycloolefin polymer, polycarbonate, polyacrylate, polyimide, and polyamide can be used. The thickness of the transparent substrate 2 is not particularly limited, and is preferably 10 to 200 μm, for example.

[0025] The surface of the transparent substrate 2 may be subjected to surface modification treatment to improve adhesion with other layers. Examples of surface modification treatment include alkali treatment, corona treatment, plasma treatment, sputtering treatment, application of a surfactant or silane coupling agent, and Si vapor deposition.

[0026] The hard coating layer 3 is a layer that imparts hardness to the optical film 1. The hard coating layer 3 can be formed by applying a composition containing (A) a (meth)acrylic monomer having three or more (meth)acryloyl groups in one molecule, (B) a (meth)acrylic polymer having two or more (meth)acryloyl groups in one molecule and a weight average molecular weight of 15,000 to 50,000, and (C) a thiol compound in a prescribed ratio to a transparent substrate 2 and curing it. The film thickness of the hard coating layer 3 is preferably 3 to 20 μm. When the film thickness of the hard coating layer 3 is less than 3 μm, the hardness of the hard coating layer 3 is insufficient, so it is not preferred. On the other hand, when the thickness of the hard coating layer 3 exceeds 30 μm, the bendability of the optical film 1 is reduced, and the curling caused by shrinkage during curing becomes larger, so it is not preferred.

[0027] (A) (Meth) acrylic acid monomer

[0028] (Meth)acrylic acid monomer is a component that mainly imparts hardness to the hard coat layer. As the (meth)acrylic acid monomer, a compound having three or more (meth)acryloyl groups in one molecule is used. When a (meth)acrylic acid monomer having two or less functions is used, the hardness cannot be fully expressed. The mixing ratio of the (meth)acrylic acid monomer having three or more functions is set to 60 to 90% by mass of the solid content of the composition for forming the hard coat layer. When the mixing ratio of the (meth)acrylic acid monomer having three or more functions is less than 60% by mass, the hardness of the hard coat layer may not be fully expressed. On the other hand, when the mixing ratio of the (meth)acrylic acid monomer having three or more functions exceeds 90%, strong curling is exhibited and the bending property is deteriorated.

[0029] Examples of trifunctional or higher (meth)acrylic monomers include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate, glycerol tri(meth)acrylate and the like tri(meth)acrylate; pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, di(trimethylolpropane) tri(meth)acrylate and the like tri(meth)acrylate; Ester compounds; polyfunctional (meth)acrylate compounds having three or more functions such as pentaerythritol tetra(meth)acrylate, di(trimethylolpropane) tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, di(trimethylolpropane) penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and di(trimethylolpropane) hexa(meth)acrylate; and polyfunctional (meth)acrylate compounds in which a part of these (meth)acrylates is substituted with alkyl groups or ε-caprolactone, etc.

[0030] In addition, as the (meth)acrylic monomer, urethane (meth)acrylate may also be used. Examples of the urethane (meth)acrylate include urethane (meth)acrylates obtained by reacting a (meth)acrylate monomer having a hydroxyl group with a product obtained by reacting an isocyanate monomer or a prepolymer with a polyester polyol.

[0031] Examples of urethane (meth)acrylates include pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate isophorone diisocyanate urethane prepolymer, and dipentaerythritol pentaacrylate isophorone diisocyanate urethane prepolymer.

[0032] As the (meth)acrylic acid monomer, any one of the above compounds may be used, or two or more of them may be used in combination.

[0033] Specific examples of the (meth)acrylic monomer include Light Acrylate PE-3A (pentaerythritol triacrylate), Light Acrylate TMP-A (trimethylolpropane triacrylate), and Light Acrylate DPE-6A (dipentaerythritol hexaacrylate) manufactured by Kyoeisha Chemical Co., Ltd.

[0034] (B) (Meth) acrylic acid polymer

[0035] (Meth)acrylic polymer is a component that mainly imparts low curling and bendability. As a (meth)acrylic polymer, a compound having two or more (meth)acryloyl groups in one molecule and a weight average molecular weight of 15,000 to 50,000 can be used. (Meth)acrylic polymers with two or more functions are entangled with each other to form a network. The network of the (meth)acrylic polymer becomes the skeleton of the adhesive, thereby being able to suppress curling and improve bendability. In addition, the above-mentioned (meth)acrylic monomer enters the gaps in the network of the (meth)acrylic polymer to cross-link the polymers. As a result, the polymerization density is increased and the hardness is increased. When the weight average molecular weight of the (meth)acrylic polymer is less than 15,000, the (meth)acrylic polymer cannot fully constitute the above-mentioned network, and the curling suppression ability and bendability are reduced, so it is not preferred. On the other hand, when the weight average molecular weight of the (meth)acrylic polymer exceeds 50,000, the compatibility of the composition used to form the hard coating layer deteriorates, so it is not preferred.

[0036] The proportion of the (meth)acrylic polymer having two or more functional groups is set to 5 to 35% by mass of the solid content of the composition for forming the hard coat layer. If the proportion of the (meth)acrylic polymer having two or more functional groups is less than 5% by mass, sufficient low curling and bending properties cannot be obtained, which is not preferred. On the other hand, if the proportion of the (meth)acrylic polymer having two or more functional groups exceeds 35% by mass, the hardness of the hard coat layer decreases, which is not preferred.

[0037] As the (meth)acrylic polymer, for example, SMP-250AP (acrylic acid equivalent: 240 to 260 g / eq, weight average molecular weight: 20,000 to 30,000), SMP-360AP (acrylic acid equivalent: 350 to 370 g / eq, weight average molecular weight: 20,000 to 30,000), and SMP-550AP (acrylic acid equivalent: 540 to 560 g / eq, weight average molecular weight: 20,000 to 30,000) manufactured by Kyoeisha Chemical Co., Ltd., which have a (meth)acryloyl group and a hydroxyl group in the side chain, can be used.

[0038] (C) Thiol compounds

[0039] The thiol compound is a component that functions as a curing aid. The mixing ratio of the thiol compound is set to 0.5 to 9% by mass of the solid content of the composition for forming the hard coat layer. By adding a small amount of the thiol compound, the curability of the (meth) acrylic acid monomer and the (meth) acrylic acid polymer can be improved, and the hardness of the hard coat layer can be improved. The thiol compound particularly improves the curability of the (meth) acrylic acid monomer.

[0040] Furthermore, by adding a thiol compound, a mercapto group is introduced into the adhesive matrix, thereby improving low curling property and bendability. As the thiol compound, a compound having two or more mercapto groups in one molecule is preferably used because it improves low curling property and bendability.

[0041] When the mixing ratio of the thiol compound is less than 0.5% by mass, the effect of improving the low curling property and the bending property becomes small due to the small mixing ratio, so it is not preferred. In addition, when the mixing ratio of the thiol compound is small, the function as a curing aid is insufficient. On the other hand, when the mixing ratio of the thiol compound exceeds 9% by mass, although the low curling property and the bending property are further improved, the hardness of the hard coat layer is significantly reduced, so it is not preferred.

[0042] Specific examples of the thiol compound include Karenz MT (registered trademark) BD-1 (1,4-bis(3-mercaptobutyryloxy)butane) and Karenz MT (registered trademark) PE-1 (pentaerythritol tetrakis(3-mercaptobutyrate)) manufactured by Showa Denko Industries, Ltd.

[0043] (D) Photopolymerization initiator

[0044] In order to be able to utilize ultraviolet rays for polymerization curing, a photopolymerization initiator is added to the composition for forming a hard coat. As a photopolymerization initiator, free radical polymerization initiators such as acetophenone, benzophenone, thioxanthone, benzoin, and benzoin methyl ether can be preferably used. For example, as a photopolymerization initiator, 2,2-ethoxyacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2,2-dimethoxy-phenylacetophenone, dibenzoyl, benzoin, benzoin methyl ether, benzoin ethyl ether, p-chlorobenzophenone, p-methoxybenzophenone, Michler's ketone, acetophenone, 2-chlorothioxanthone, etc. can be used. One of them can be used alone, or two or more can be used in combination. As a commercially available photopolymerization initiator, for example, Omnirad 184 (1-hydroxycyclohexyl phenyl ketone) manufactured by IGM RESIN can be used, Omnirad 651 (2,2-dimethoxyphenylacetophenone). The mixing ratio of the photopolymerization initiator is preferably 0.1 to 10.0% by mass of the solid content of the composition for forming the hard coat layer.

[0045] (E) Leveling agent

[0046] In order to improve the planarity of the coating film of the composition for forming the hard coat layer, a leveling agent may also be added. The mixing ratio of the leveling agent is preferably 0.05 to 5.0% by mass of the solid content of the composition for forming the hard coat layer. The compound that can be used as the leveling agent is not particularly limited, and for example, KY-1203 manufactured by Shin-Etsu Chemical Co., Ltd. can be used.

[0047] In addition, a solvent may be appropriately added to the composition for forming the hard coating. As the solvent, one of the following solvents may be used or a mixture of two or more thereof: alcohols such as methanol, ethanol, 1-propanol, 2-propanol, butanol, isopropanol, and isobutanol; ketones such as acetone, methyl ethyl ketone, cyclohexanone, and methyl isobutyl ketone; ketone alcohols such as diacetone alcohol; aromatic hydrocarbons such as benzene, toluene, and xylene; glycols such as ethylene glycol, propylene glycol, and hexylene glycol; glycol ethers such as ethyl cellosolve, butyl cellosolve, ethyl carbitol, butyl carbitol, diethyl cellosolve, diethyl carbitol, and propylene glycol monomethyl ether; esters such as methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, and amyl acetate; ethers such as dimethyl ether and diethyl ether; N-methylpyrrolidone, dimethylformamide, and water.

[0048] Furthermore, the hard coat layer forming composition may contain monomers other than those described above, oligomers, polymers, defoamers, antioxidants, ultraviolet absorbers, light stabilizers, polymerization inhibitors, photosensitizers and other additives as necessary.

[0049] The optical film 1 of this embodiment can be used to be attached to the outermost surface of an image display panel such as a liquid crystal panel and an organic EL panel to form an image display device. A touch panel can also be provided between the optical film 1 and the image display panel. In addition, the optical film 1 can also be used as a protective film for a polarizing plate provided by the image display device. The optical film 1 of this embodiment is suitable for a portable terminal provided with a foldable image display device because of its excellent hardness and bendability. In addition, the optical film 1 of this embodiment is excellent in processability when manufacturing an image display device because of its suppressed curling.

[0050] In addition, in the above-mentioned embodiment, a hard coating film in which a hard coating layer 3 is laminated on one surface of a transparent substrate 2 is described as an example, but it is also possible to have an optical film structure in which a hard coating layer 3 is laminated on both surfaces of a transparent substrate 2. In addition, it is also possible to have an optical film structure in which, in addition to the hard coating layer 3, one or more functional layers such as an anti-glare layer, a low-reflection layer, a high-refractive index layer, a medium-refractive index layer, an antistatic layer, an electromagnetic wave shielding layer, an infrared absorption layer, an ultraviolet absorption layer, a color correction layer, and an antifouling layer are laminated on the transparent substrate 2.

[0051] Example

[0052] Hereinafter, examples in which the present invention is specifically implemented will be described.

[0053] The materials used in Examples and Comparative Examples are as follows.

[0054] (A) (Meth) acrylic acid monomer

[0055] (A-1) Light Acrylate PE-3A (pentaerythritol triacrylate), Kyoeisha Chemical Co., Ltd.

[0056] (A-2) Light Acrylate 3EG-A (triethylene glycol diacrylate), Kyoeisha Chemical Co., Ltd.

[0057] (B) (Meth) acrylic acid polymer

[0058] (B-1) SMP-250AP, weight average molecular weight 20,000 to 30,000, Kyoeisha Chemical Co., Ltd.

[0059] (B-2) Light Acrylate 9EG-A (PEG400# diacrylate), weight average molecular weight of 1000 or less, Kyoeisha Chemical Co., Ltd.

[0060] (B-3) Urethane Acrylate BPZA-66, weight average molecular weight: about 100,000, Kyoeisha Chemical Co., Ltd.

[0061] (C) Thiol compounds

[0062] Karenz MT (registered trademark) PE-1 (pentaerythritol tetrakis(3-mercaptobutyrate)), Showa Denko K.K.

[0063] (D) Photopolymerization initiator

[0064] Omnirad 184 (1-Hydroxycyclohexylphenyl ketone), IGM RESIN

[0065] (E) Leveling agent

[0066] KY-1203, Shin-Etsu Chemical Co., Ltd.

[0067] The composition for forming a hard coat layer of the composition shown in Table 1 was applied to the surface of a polyimide substrate (50 μm thick) by a bar coating method, dried, and then irradiated with a high pressure mercury lamp at a dose of 200 mJ / m 2 The coating was cured by irradiation with ultraviolet light to obtain the optical films of each embodiment and each comparative example. In addition, the composition for forming the hard coating layer was diluted with methyl isobutyl ketone to a total solid content concentration of 40% by mass. In addition, the amount of the composition for forming the hard coating layer was adjusted so that the film thickness after curing was the value described in Table 1.

[0068] Using the optical films of each Example and each Comparative Example, pencil hardness, curling, and bending properties were evaluated by the following methods.

[0069] <Pencil hardness>

[0070] The pencil hardness is measured in accordance with JIS K5400-1900. The pencil hardness of the hard coating surface is measured using a pencil (uni, manufactured by Mitsubishi Pencil Co., Ltd.) and a Clemen type scratch tester (HA-301, manufactured by TESTER SANGYO CO,.LTD.). The test is repeated while changing the hardness of the pencil, and the change in appearance caused by the scratch is visually observed. The maximum hardness at which no scratch is observed is used as the evaluation value. The evaluation criteria are as follows.

[0071] ◎:6H or above

[0072] 0: 5H

[0073] △: 4H

[0074] ×: 3 hours or less

[0075] <Curly>

[0076] The optical film was cut into a 100 mm square sample, and the sample was placed on a plane. The vertical distance from the plane to the top of the four corners was measured in mm, and the average of the measured values ​​of the four corners was used as the evaluation value. The smaller the evaluation value, the smaller the curl. The evaluation criteria are as follows.

[0077] ◎: 10mm or less

[0078] ○: More than 10 mm and less than 20 mm

[0079] △: More than 20mm and less than 35mm

[0080] ×: more than 35mm

[0081] <Flexibility>

[0082] The optical film was cut into a sample with a width of 30 mm, and the sample was fixed to a Clamshell bending tester (DR11MR-CS-t, manufactured by YUASA SYSTEM Co., Ltd.) with the hard coating layer on the outside, and subjected to a 200,000-cycle repeated bending test. The bending diameter in mm that can be subjected to the 200,000-cycle repeated bending test was determined according to the following criteria.

[0083] ◎:5mm or less

[0084] ○: More than 5mm and less than 10mm

[0085] △: more than 10m and less than 15mm

[0086] ×: more than 15 mm

[0087] Table 1 shows the compositions of the hard coat layer-forming compositions of Examples and Comparative Examples and the evaluation results of the pencil hardness, curling, and bendability.

[0088]

[0089] As shown in Table 1, the pencil hardness, curling, and bendability of the optical films of Examples 1 to 6 were all evaluated as ◯ or more, and the pencil hardness, curling, and bendability were all good.

[0090] Since the optical film of Comparative Example 1 has a small blending ratio of the (meth)acrylic monomer, the pencil hardness is low.

[0091] Since the optical film of Comparative Example 2 had a large blending ratio of the (meth)acrylic monomer, it had large curling and low bendability.

[0092] Since the optical film of Comparative Example 3 has a large blending ratio of the thiol compound, the pencil hardness is low.

[0093] Since the optical film of Comparative Example 4 did not contain a (meth)acrylic polymer and a thiol compound, the curling became large and the bendability became low.

[0094] Since the optical film of Comparative Example 5 does not contain a (meth)acrylic monomer, the pencil hardness is low.

[0095] Since the optical films of Comparative Examples 6 and 7 did not contain a (meth)acrylic polymer, curling became large and bendability became low.

[0096] The optical film of Comparative Example 8 is formed with a hard coating layer using a composition for forming a hard coating layer without a thiol compound. Comparison of Comparative Example 8 with Example 4 (the proportions of (meth)acrylic acid monomer and (meth)acrylic acid polymer are substantially the same) shows that since no thiol compound is added to the composition for forming a hard coating layer, the curling becomes larger and the bending property becomes lower. In addition, the proportion of the (meth)acrylic acid monomer in Comparative Example 8 is greater than that in Example 4, but no thiol compound that functions as a curing aid is added to the composition for forming a hard coating layer, so the pencil hardness is lower than that in Example 4.

[0097] The optical film of Comparative Example 9 is formed with a hard coating layer using a composition for forming a hard coating layer without a thiol compound. Comparison of Comparative Example 9 with Example 1 (the mixing ratio of the (meth)acrylic monomer and the (meth)acrylic polymer is substantially the same) shows that since the composition for forming a hard coating layer does not contain a thiol compound that functions as a curing aid, the pencil hardness is lower than that of Example 1. In addition, the curling and bending properties in Comparative Example 9 are evaluated as "○" because the mixing amount of the (meth)acrylic monomer that deteriorates the curling and bending properties in exchange for hardness is substantially the same as that of Example 1 and is less than that of Comparative Example 8.

[0098] Since the optical film of Comparative Example 10 used a bifunctional (meth)acrylic monomer, the pencil hardness was low.

[0099] The optical film of Comparative Example 11 has a larger curl and lower bendability due to the use of a low molecular weight polymerizable compound instead of a (meth) acrylic polymer. This is believed to be because a polymer network serving as a skeleton is not formed because a long-chain (meth) acrylic polymer is not incorporated into the composition for forming the hard coat layer.

[0100] The optical film of Comparative Example 12 has a low pencil hardness due to the use of a polymerizable compound having a molecular weight of 100,000 as the (meth)acrylic polymer. This is believed to be because the molecular weight of the (meth)acrylic polymer used is too large, which deteriorates the compatibility of the composition for forming the hard coating layer and causes uneven distribution of the components.

[0101] The optical film of Comparative Example 13 had a thin hard coat layer, and thus had a low pencil hardness.

[0102] The optical film of Comparative Example 14 had a thick hard coat layer, so curling became large and the bendability decreased.

[0103] Possibility of Industrial Application

[0104] The present invention can be used for an optical film used in an image display device.

[0105] Explanation of symbols

[0106] 1 Optical film

[0107] 2 Transparent substrate

[0108] 3 Hard coating

Claims

1. An optical film having a hard coating layer on at least one surface of a transparent substrate, in, The hard coating layer is a cured film of a composition comprising (A) a (meth)acrylic monomer having three or more (meth)acrylic groups in one molecule, (B) a (meth)acrylic polymer having two or more (meth)acrylic groups in one molecule and a weight average molecular weight of 15,000 to 50,000, and (C) a thiol compound. In the total solid content of the composition, the content ratio of the (meth)acrylic acid monomer is 60 to 85% by mass, the content ratio of the (meth)acrylic acid polymer is 5 to 35% by mass, and the content ratio of the thiol compound is 0.5 to 9% by mass. The hard coating layer has a thickness of 3 to 20 μm.

2. The optical film according to claim 1, in, The thiol compound has two or more mercapto groups in one molecule.

3. The optical film according to claim 1, in, The transparent substrate is formed of any one of triacetyl cellulose, polyethylene naphthalate, polyethylene terephthalate, cycloolefin polymer, polycarbonate, polyacrylate, polyimide, and polyamide.

4. The optical film according to claim 2, in, The transparent substrate is formed of any one of triacetyl cellulose, polyethylene naphthalate, polyethylene terephthalate, cycloolefin polymer, polycarbonate, polyacrylate, polyimide, and polyamide. 5 . An image display device comprising the optical film according to claim 1 .

Citation Information

Patent Citations

  • Resin composite for forming hard coat layer

    CN102482529A

  • Hard-coating film for display device, and display device comprising same

    CN107820503A

  • Hard coat laminated film

    CN109922959A

  • Plastic laminate and image display protecting film

    JP2000141556A

  • Hard coating agent composition and molded product

    JP2006316249A